PENGARUH KARAKTERISTIK INDIVIDU DAN ETOS KERJA TERHADAP EFEKTIVITAS PENYELESAIAN PERKARA PADA SATUAN RESKRIM POLRES JEMBRANA - LATIF, MUH. WAHYUDIN (Fakultas Hukum Universitas Dwijendra, 2015)
ABSTRAKThe main task of the police is to maintain public order and law enforcement. Affirmation of special police powers in performing police duties governed by Article 2 of Law No. 2 of 2002 on the Indonesian National Police. Police must act professionally and holds the code of conduct strictly and hard, so it is not easy to fall to the hated spectrum of society. On behalf of the law, the police were given greater authority. In fact, this authority is not given to any institution to force even curb freedoms and human rights, among others, capture, detain, search, seize, ordered to stop, prohibit people leave the place, checking the identity of a specific person. The main problem in this paper is